Introduction: when security meet politics of conflict, women, development and peace, get ready for a challenging year - Chen, Mumin; Zarina Othman,; Bakri Mat, (Penerbit Universiti Kebangsaan Malaysia, 2022)
This editorial note serves as an introductory explanation as we approach the dawn of 2023. The hardship of a total lockdown changes how we look at space and time or spatiotemporal beyond ordinary linearity of progress and regress. Nevertheless, how do we use space and time to make sense of the most significant concerns of threats to our security? How do we refine constructive ideas about safety and inspire others to think beyond the rigidity of rational choice and nearly no freedom to choose? Time and space transform our perceived secured reality and insinuate threat discursively, whether yesterday or today, international, or local. In our nested security discourse, we challenge the archaic and unstable binary boundaries between international and internal delineation of security threats and peace concerns. Altogether, temporal constraints and limited space disperse our cognitive inability to operate within the tesseract of multiple data analytics, eternal realities, and organic, meaningful solutions to give hope to humanity and freedom to coexist mutually. Underpinned by multidimensions and nested security discourse, we present our readers with our final thoughts in selecting six research articles, three research notes, two commentaries, and one book review.